Análise da implementação do centro de justiça restaurativa da Defensoria Pública do estado do Ceará na apuração de ato infracional em Fortaleza no período de 2017 a 2023. - Pedrosa, Antonio Renato Gonçalves (2024)
Restorative Justice in Brazil originated in the Children’s and Adolescents’ Rights formalized by Law No. 12,594 of January 18, 2012. The model, which emphasizes care for victims, accountability for offenders, and reparation to the degree possible, is constantly evolving in various regions of the country. In 2016, the National Council of Justice recognized Restorative Justice as a public policy within the Judiciary. And, in November 2017, the Public Defender's Office of the State of Ceará began a pioneering project that aims to offer restorative practices as an alternative to the traditional judicial process for the verification of criminal acts, specifically in the 5th Court of Children and Adolescents of Fortaleza, Ceará. This project was implemented through the Restorative Justice Center and was consolidated as an institutional policy in 2020. That said, this study analyzes advances and challenges in Restorative Justice from November 2017 to December 2023, including the use of circle process and peacebuilding initiatives. Furthermore, it investigates whether the applied Restorative Justice methodology actually holds adolescents accountable, meets the needs of victims, and provides protagonism to the parties involved in the criminal acts. The research is bibliographic in nature, including consultation of books, webinars, and scientific articles. In addition, it includes documentary analysis of resolutions, legislation, and technical reports, complemented by self-assessment and field monitoring by the author. Finally, the study proves the effectiveness of Restorative Justice, highlighting the advances and improvements in the process of holding juvenile offenders accountable from this perspective. In addition, ten recommendations are presented to improve, expand, and consolidate the restorative paradigm.